2012
DOI: 10.1038/hdy.2012.88
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlation between the pre-adult developmental period and locomotor activity rhythm in Drosophila melanogaster

Abstract: Biological clocks regulate various behavioural and physiological traits; slower circadian clocks are expected to slow down the development, suggesting a potential genetic correlation between the developmental period and circadian rhythm. However, a correlation between natural genetic variations in the developmental period and circadian rhythm has only been found in Bactrocera cucurbitae. The number of genetic factors that contribute to this genetic correlation is largely unclear. In this study, to examine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Correlation between development time and circadian clocks was also reported in laboratory selection studies on melon flies (Miyatake, 1997b;Shimizu et al, 1997) and fruit flies (Kumar et al, 2006;Takahashi et al, 2013;Yadav and Sharma, 2013a). Disruption of circadian timing systems results in reduced reproductive output in the gypsy moth, Lymantria dispar (Giebultowicz et al, 1990), and D. melanogaster (Beaver et al, 2002;Beaver et al, 2003), shortening of adult lifespan in D. melanogaster (Hendricks et al, 2003;Kumar et al, 2005), reduction in vegetative growth and survivorship in Arabidopsis thaliana (Dodd et al, 2005), and increased predation in free-living ground squirrels Spermophilus lateralis (DeCoursey et al, 1997) and chipmunks Tamias striatus (DeCoursey et al, 2000).…”
Section: Introductionsupporting
confidence: 55%
“…Correlation between development time and circadian clocks was also reported in laboratory selection studies on melon flies (Miyatake, 1997b;Shimizu et al, 1997) and fruit flies (Kumar et al, 2006;Takahashi et al, 2013;Yadav and Sharma, 2013a). Disruption of circadian timing systems results in reduced reproductive output in the gypsy moth, Lymantria dispar (Giebultowicz et al, 1990), and D. melanogaster (Beaver et al, 2002;Beaver et al, 2003), shortening of adult lifespan in D. melanogaster (Hendricks et al, 2003;Kumar et al, 2005), reduction in vegetative growth and survivorship in Arabidopsis thaliana (Dodd et al, 2005), and increased predation in free-living ground squirrels Spermophilus lateralis (DeCoursey et al, 1997) and chipmunks Tamias striatus (DeCoursey et al, 2000).…”
Section: Introductionsupporting
confidence: 55%
“…For example, strains of the melon fly Bactrocera cucurbitae artificially selected for a shorter developmental period had shorter free-running periods of circadian rhythm than did strains selected for a longer developmental period (Shimizu, Miyatake, Watari, & Arai, 1997). The same phenomenon was also seen in Drosophila melanogaster (Kumar, Kumar, Paranjpe, Akarsh, & Sharma, 2007;Takahashi, Teramura, Muraoka, Okada, & Miyatake, 2013). These studies suggest correlations between life history traits and the free-running period of circadian rhythm.…”
Section: Introductionmentioning
confidence: 76%
“…Circadian ( circa = about ; dies = a day ) clocks with near 24‐h periodicities regulate behavioral and metabolic processes in a wide variety of organisms (Saunders, ; Dunlap et al ., ). In insects including fruit flies Drosophila melanogaster , these clocks have also been implicated in the regulation of life‐history traits such as preadult development time and adult lifespan (Kyriacou et al ., ; Miyatake, , ; Shimizu et al ., ; Klarsfeld & Rouyer, ; Sheeba et al ., ; Paranjpe et al ., ; Takahashi et al ., ; Yadav & Sharma, 2013, 2014). It is believed that preadult development time of flies with faster circadian clocks is shorter than those with slower clocks.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that preadult development time of flies with faster circadian clocks is shorter than those with slower clocks. While this proposal still awaits rigorous and unequivocal empirical support, previous studies in fruit flies D. melanogaster (Kyriacou et al ., ; Paranjpe et al ., ; Kumar et al ., ; Takahashi et al ., ; Yadav & Sharma, 2013), and in melon flies Bactrocera cucurbitae (Miyatake, , ; Shimizu et al ., ) have shown that the period of circadian activity/rest rhythm is correlated with the egg‐to‐adult duration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation